An introduction to passive radar - Griffiths, H. (Hugh), 1956-; Baker, Christopher J., (Radar specialist) (Boston : Artech House, 2017)
This resource introduces the basic principles of passive radar technology and provides an overview of recent developments in this field and existing real passive radar systems. this book explains how passive radar works, how it differs from the active type, and demonstrates the benefits and drawbacks of this novel technology. Properties of illuminators, including ambiguity functions, digital vs. analog, digitally coded waveforms, vertical-plane coverage, and satellite-borne and radar illuminators are explored.
Introduction -- Principles of passive radar -- Properties of illuminators -- Direct signal suppression -- Passive radar performance prediction -- Detection and tracking -- Examples of systems and results -- Future developments and applications.
Includes bibliographical references and index.
Keywords: Bistatic radar; Tracking radar; Bistatic radar; Tracking radar